The effects of plyometric jump training on physical fitness attributes in basketball players: A meta-analysis - Ramirez-Campillo, Rodrigo; García-Hermoso, Antonio; Moran, Jason; Chaabene, Helmi; Negra, Yassine; Scanlan, Aaron T. (Journal of sport and health science, 2022)
•Plyometric jump training improves jumping performance, linear sprint speed, change-of-direction speed, balance, and muscle strength in basketball players, regardless of sex and age.•Programmable training variables such as plyometric jump training program duration, session frequency, and total number of sessions do not moderate the beneficial effects of plyometric jump training on physical fitness attributes in basketball players.•Greater improvements in horizontal jump distance, linear sprint speed, and change-of-direction speed were evident among older (>16.3 years) compared to younger basketball players (≤16.3 years). There is a growing body of experimental evidence examining the effects of plyometric jump training (PJT) on physical fitness attributes in basketball players; however, this evidence has not yet been comprehensively and systematically aggregated. Therefore, our objective was to meta-analyze the effects of PJT on physical fitness attributes in basketball players, in comparison to a control condition. A systematic literature search was conducted in the databases PubMed, Web of Science, and Scopus, up to July 2020. Peer-reviewed controlled trials with baseline and follow-up measurements investigating the effects of PJT on physical fitness attributes (muscle power, i.e., jumping performance, linear sprint speed, change-of-direction speed, balance, and muscle strength) in basketball players, with no restrictions on their playing level, sex, or age. Hedge's g effect sizes (ES) were calculated for physical fitness variables. Using a random-effects model, potential sources of heterogeneity were selected, including subgroup analyses (age, sex, body mass, and height) and single training factor analysis (program duration, training frequency, and total number of training sessions). Computation of meta-regression was also performed. Thirty-two studies were included, involving 818 total basketball players. Significant (p < 0.05) small-to-large effects of PJT were evident on vertical jump power (ES = 0.45), countermovement jump height with (ES = 1.24) and without arm swing (ES = 0.88), squat jump height (ES = 0.80), drop jump height (ES = 0.53), horizontal jump distance (ES = 0.65), linear sprint time across distances ≤10 m (ES = 1.67) and >10 m (ES = 0.92), change-of-direction performance time across distances ≤40 m (ES = 1.15) and >40 m (ES = 1.02), dynamic (ES = 1.16) and static balance (ES = 1.48), and maximal strength (ES = 0.57). The meta-regression revealed that training duration, training frequency, and total number of sessions completed did not predict the effects of PJT on physical fitness attributes. Subgroup analysis indicated greater improvements in older compared to younger players in horizontal jump distance (>17.15 years, ES = 2.11; ≤17.15 years, ES = 0.10; p < 0.001), linear sprint time >10 m (>16.3 years, ES = 1.83; ≤16.3 years, ES = 0.36; p = 0.010), and change-of-direction performance time ≤40 m (>16.3 years, ES = 1.65; ≤16.3 years, ES = 0.75; p = 0.005). Greater increases in horizontal jump distance were apparent with >2 compared with ≤2 weekly PJT sessions (ES = 2.12 and ES = 0.39, respectively; p < 0.001). Data from 32 studies (28 of which demonstrate moderate-to-high methodological quality) indicate PJT improves muscle power, linear sprint speed, change-of-direction speed, balance, and muscle strength in basketball players independent of sex, age, or PJT program variables. However, the beneficial effects of PJT as measured by horizontal jump distance, linear sprint time >10 m, and change-of-direction performance time ≤40 m, appear to be more evident among older basketball players. [Display omitted]